Introduction to research in education - Ary, Donald (Holt, Rinehart and Winston, 2006)
Instructor's manual with test bank for introduction to research in education. seventh edition by donald ary lucy jacobs chris sorensen and dan mccollum. Hard to obtain copy!!!